China's peaceful rise speeches of Zheng Bijian, 1997-2005. - Zheng, Bijian (Brookings Institution Press, 2005)
"Leading Chinese thinker explains his theory of China's development path, based not on territorial expansion or challenges to other powers, but on its own hard work and a mutually beneficial international environment"--Provided by publisher.